LPS-induced expression of CD14 in the TRIF pathway is epigenetically regulated by sulforaphane in porcine pulmonary alveolar macrophages. Issue 8 (November 2016) - Yang, Qin; Pröll, Maren J; Salilew-Wondim, Dessie; Zhang, Rui; Tesfaye, Dawit; Fan, Huitao; Cinar, Mehmet U; Große-Brinkhaus, Christine; Tholen, Ernst; Islam, Mohammad A; Hölker, Michael; Schellander, Karl; et al.
Pulmonary alveolar macrophages (AMs) are important in defense against bacterial lung inflammation. Cluster of differentiation 14 (CD14) is involved in recognizing bacterial lipopolysaccharide (LPS) through MyD88-dependent and TRIF pathways of innate immunity. Sulforaphane (SFN) shows anti-inflammatory activity and suppresses DNA methylation. To identify CD14 epigenetic changes by SFN in the LPS-induced TRIF pathway, an AMs model was investigated in vitro . CD14 gene expression was induced by 5 µg/ml LPS at the time point of 12 h and suppressed by 5 µM SFN. After 12 h of LPS stimulation, gene expression was significantly up-regulated, including TRIF, TRAF6, NF-κB, TRAF3, IRF7, TNF-α, IL-1β, IL-6, and IFN-β. LPS-induced TRAM, TRIF, RIPK1, TRAF3, TNF-α, IL-1β and IFN-β were suppressed by 5 µM SFN. Similarly, DNMT3a expression was increased by LPS but significantly down-regulated by 5 µM SFN. It showed positive correlation of CD14 gene body methylation with in LPS-stimulated AMs, and this methylation status was inhibited by SFN. This study suggests that SFN suppresses CD14 activation in bacterial inflammation through epigenetic regulation of CD14 gene body methylation associated with DNMT3a. The results provide insights into SFN-mediated epigenetic down-regulation of CD14 in LPS-induced TRIF pathway inflammation and may lead to new methods for controlling LPS-induced inflammation in pigs.